Thin Film Model Systems: Thin Film NCM Cathodes as Model Systems to Assess the Influence of Coating Layers on the Electrochemical Performance of Lithium Ion Batteries (Adv. Mater. Interfaces 9/2021). Issue 9 (7th May 2021) - Hemmelmann, Hendrik; Dinter, Julius K.; Elm, Matthias T.
Abstract : Thin film model systems allow to analyse the properties of cathode materials without the influence of additives. In article number 2002074, Matthias T. Elm and co‐workers demonstrate that probing the cathode‐electrolyte‐interface of pristine and coated NCM thin films with surface sensitive techniques enables to elucidate the beneficial effect of protective layers.